International cooperation to fight terrorism: a study of laws and diplomacy on the global stage - Skrāģe, Elīza Marta (Riga Graduate School of Law, 2024)
Despite being a name that evokes dread, terrorism is a common occurrence throughout the globe and may take many different forms. From a practical standpoint, it is evident that involvement in terrorist actions, groups, financing, and idea dissemination inside society is both unacceptable and illegal. The existence of specific articles, conventions, and resolutions, however, is still insufficient; as a result, the nations must establish a certain level of confidence and communication with one another. Diplomacy plays a crucial role in ensuring this. In light of this, the goal of this paper was to determine whether fighting terrorism is feasible not just "on paper," but also practically and realistically; what obstacles nations and organizations face; and what else could be done to potentially increase the effectiveness of counterterrorism efforts.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Comparative law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Terrorism; Counter-terrorism